1974
DOI: 10.1530/acta.0.0770128
|View full text |Cite
|
Sign up to set email alerts
|

Light Synchronization of the Circadian Rhythm of Plasma 11-Hydroxycorticosteroids in Man

Abstract: The levels of plasma 11-hydroxycorticosteroids were studied in 4 healthy subjects with a constant sleep-waking cycle and a constant activity schedule before and after experimental alteration of the dark-light cycle. The subjects slept in the dark from 10.30 p. m. to 6.30 a. m. During a control period of 10 days the subjects stayed in rooms which were well lighted after 6.30 a. m. During the following 10 days darkness was prolonged by 4 h until 10.30 a. m. Hourly blood samples were obtained from 2.30 to 11.30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The stress may have been more intense during the control period, which in all subjects preceded the experimental period. How¬ ever, it is conceivable that the stress was more intense during the experimental period when the subjects remained in complete darkness for an extra 4 h. Furthermore, the average levels of 11-hydroxycorticosteroids during both periods of investigation were similar, which indicated that the possible dif¬ ference in stress was minimal (Osterman 1974).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The stress may have been more intense during the control period, which in all subjects preceded the experimental period. How¬ ever, it is conceivable that the stress was more intense during the experimental period when the subjects remained in complete darkness for an extra 4 h. Furthermore, the average levels of 11-hydroxycorticosteroids during both periods of investigation were similar, which indicated that the possible dif¬ ference in stress was minimal (Osterman 1974).…”
Section: Discussionmentioning
confidence: 93%
“…The negligible influence of changes in the dark-light pattern, on the synchronization of the sleep-related changes in the prolactin level, contrasts with the findings of studies on the circadian plasma cortisol rhythm. In man the dark-light transition seems to be important for the synchronization of the circadian plasma cortisol rhythm (Orth Sc Island 1969;Osterman 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol secretion is regulated by the circadian rhythm, which is influenced by external cues called zeitgebers, such as light-dark cycle,[ 5 6 ] awakening[ 7 ] and social cues. [ 8 ] Light, in particular, plays a crucial role in the entrainment of the circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%